2016
DOI: 10.1016/j.ygyno.2015.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Micro-RNAs associated with the evolution of ovarian cancer cisplatin resistance

Abstract: Objectives Ovarian cancer (OVCA) is the leading cause of mortality among women with gynecologic malignancy, in part due to the development of chemoresistance. We sought to identify micro-RNAs (miRNAs) associated with in vitro development of OVCA chemoresistance that may also represent potential targets for therapy. Methods In this study, four OVCA cell lines (A2780CP, A2780S, IGROV1, and OVCAR5) were serially treated with cisplatin in parallel with measurements of miRNA expression changes. Results Nine miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…These data suggest that miR-31-5p can mediate OXA resistance. Previous studies informed us that miRNAs can mediate cellular sequestration through the mediation of multidrug-resistant proteins and the alteration of calcium signaling [ 32 34 ]. In this study, further fractionation of cellular components revealed a change in lysosomal accumulation, which promoted the expression of possible drug transporters that were bound to lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that miR-31-5p can mediate OXA resistance. Previous studies informed us that miRNAs can mediate cellular sequestration through the mediation of multidrug-resistant proteins and the alteration of calcium signaling [ 32 34 ]. In this study, further fractionation of cellular components revealed a change in lysosomal accumulation, which promoted the expression of possible drug transporters that were bound to lysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…miR-9 inhibits the proliferation, migration, and invasion of serous OVCa cells by blocking TLN1-mediated FAK/AKT pathway [ 44 ]. In addition, expression of miR-496, miR-152, miR-422b, and miR17-3p correlates with acquired cisplatin resistance [ 45 ]. The current study demonstrates that miR-551b is over 100-fold higher in the SP cells than in the non-SP population of cells, implicating that this microRNA is required to maintain the phenotypic features of the SP cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin (DDP) is a cell cycle non-specific antineoplastic drug, which is applicable for the treatment of several types of cancers and it is also recommended to applied to chemotherapy for epithelial malignancies, such as lung cancer [ 14 ], ovarian cancer [ 15 ], testicular cancer [ 16 ] and cervical cancer [ 17 ]. DDP and its derivatives have been found to have encouraging anti-cancer effects on different types of cancers [ 18 ].…”
Section: Introductionmentioning
confidence: 99%